Real-time Monitoring IoT-based System for Early Flash Flood Notification in Melaka - Nahar, Haniza; Bahaman, Nazrulazhar; Md. Shah, Wahidah; Abdul-Aziz, Azlianor; Khalid, Arief Muizzuddin; Hassan, Aslinda; Ahmad, Mohd Riduan (Multidisciplinary Applied Research and Innovation, 2022)
Flash flood is a type of flooding that possibly happen within three hours of heavy rainfall. A couple of years back, flash flood often occurs in the urban areas of Wilayah Persekutuan, Selangor, Negeri Sembilan, and Melaka. This tragedy caused more than 1,000 residents have been displaced from their homes. Due to this unavoidable threat, this study proposes an early warning system for flash floods in Melaka based on the type of lightning flashes that occur during heavy rainfalls. The project incorporates a smart Internet of Things (IoT) system with a web-based application for monitoring and a mobile application for early notification. This system provides flash flood monitoring and forecasting as well as a warning system with a lead time of three hours. The raw data is processed by the IoT hardware and transmitted to the centralized network access storage. A web-based dashboard system visualizes the data for monitoring and forecasting. The fast alert notification of the predicted flash floods and locations generates early warning through the mobile application.